2016
DOI: 10.1192/bjp.bp.115.167775
|View full text |Cite
|
Sign up to set email alerts
|

Eye movement desensitisation and reprocessing therapy v. stabilisation as usual for refugees: randomised controlled trial

Abstract: Directly targeting traumatic memories through 12 h of EMDR in refugee patients needing specialised treatment is safe, but is only of limited efficacy.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
61
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 34 publications
4
61
0
Order By: Relevance
“…Moreover, 3 participants reported a deterioration of symptoms and 1 of selfefficacy. Although these findings are in contradiction with the treatment aims, they are in accordance with reported deterioration rates from a previous treatment study with a comparable sample and setting (Ter Heide, Mooren, van de Schoot, de Jongh, & Kleber, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…Moreover, 3 participants reported a deterioration of symptoms and 1 of selfefficacy. Although these findings are in contradiction with the treatment aims, they are in accordance with reported deterioration rates from a previous treatment study with a comparable sample and setting (Ter Heide, Mooren, van de Schoot, de Jongh, & Kleber, 2016).…”
Section: Discussionsupporting
confidence: 84%
“…However, as mentioned, due to the number of and type of traumas as well as postmigratory stressors that trauma-affected refuges face, conclusions based on other populations do not necessarily apply to trauma-affected refugees. Several studies have previously suggested PLOS ONE that treatment effects in trauma-affected refugees are typically smaller than in other traumaaffected populations [24][25][26]45].…”
Section: Discussionmentioning
confidence: 99%
“…In addition, NET was expected to outperform non-active and active non-TF comparators for PTSD outcomes (Lambert & Alhassoon, 2015). According to direct comparisons of TF interventions (Brom, Kleber, & Defares, 1989;Nijdam, Gersons, Reitsma, De Jongh, & Olff, 2012;Ter Heide, Mooren, Van de Schoot, De Jongh, & Kleber, 2016), no significant differences were expected comparing NET with all active control conditions (non-TF and TF comparators). Finally, advancing age and female gender were hypothesized to predict larger treatment effects, while having migrated to Western countries was hypothesized to predict lower treatment effects.…”
Section: Aims and Hypothesesmentioning
confidence: 99%